Indirect calorimetry: The 6 main issues. Issue 1 (January 2021) - Achamrah, Najate; Delsoglio, Marta; De Waele, Elisabeth; Berger, Mette M.; Pichard, Claude
Summary: Background and aims: Optimal nutritional therapy, including the individually adapted provision of energy, is associated with better clinical outcomes. Indirect calorimetry is the best tool to measure and monitor energy expenditure and hence optimize the energy prescription. Similarly to other medical techniques, indications and contra-indications must be acknowledged to optimise the use of indirect calorimetry in clinical routine. Measurements should be repeated to enable adaptation to the clinical evolution, as energy expenditure may change substantially. This review aims at providing clinicians with the knowledge to routinely use indirect calorimetry and interpret the results. Method: We performed a bibliographic research of publications referenced in PubMed using the following terms: "indirect calorimetry", "energy expenditure", "resting energy expenditure", "VCO2 ", "VO2 ", "nutritional therapy". We included mainly studies published in the last ten years, related to indirect calorimetry principles, innovations, patient's benefits, clinical use in practice and medico-economic aspects. Results: We have gathered the knowledge required for routine use of indirect calorimetry in clinical practice and interpretation of the results. A few clinical cases illustrate the decision-making process around its application for prescription, and individual optimisation of nutritional therapy. We also describe the latest technical innovations and the results of tailoring nutrition therapy according to the measured energy expenditure in medico-economic benefits. Conclusion: The routine use of indirect calorimetry should be encouraged as a strategy to optimize nutrition care.